Current Laser Resurfacing Technologies: A Review that Delves Beneath the Surface - Preissig, Jason; Hamilton, Kristy; Markus, Ramsey (Seminars in Plastic Surgery, 2012)
Numerous laser platforms exist that rejuvenate the skin by resurfacing its upper layers. In varying degrees, these lasers improve the appearance of lentigines and rhytides, eliminate photoaging, soften scarring due to acne and other causes, and treat dyspigmentation. Five major classes of dermatologic lasers are currently in common use: ablative and nonablative lasers in both fractionated and unfractionated forms as well as radiofrequency technologies. The gentler nonablative lasers allow for quicker healing, whereas harsher ablative lasers tend to be more effective. Fractionating either laser distributes the effect, increasing the number of treatments but minimizing downtime and complications. In this review article, the authors seek to inform surgeons about the current laser platforms available, clarify the differences between them, and thereby facilitate the identification of the most appropriate laser for their practice.
Keywords: laser; skin; resurfacing; photorejuvenation; ablation; fractional